Disentangling “polarization in religion” - Lina Rodenhausen (Frontiers in Political Science)
This paper examines phenomena at the intersection of polarization, religion, and social media. In particular, it disentangles and highlights the concept of “polarization in religion.” Polarization is a well-studied concept in political science and it has been considered in relation to religion before. However, these attempts are usually either interested in political polarization and the role religion plays in it, or conflate socio-political attitudes and religious issues. To fully understand polarization as a phenomenon of religion, it is important to disentangle it from politics and examine the beliefs and identities that are unique to religious traditions. The focus is on the progressive and conservative characteristics that are specific to religious groups. It is proposed to conceptualize and study polarization in religion as the construction of new religious identities. A collective identity approach can be used to examined how “progressive religious” and “conservative religious” emerge as distinct and coherent identities. Identity formation is facilitated in digital space, which is one of the reasons why polarization in religion is conceptualized as inherently involving social media. Social media in general can contribute to polarization, and contemporary religion in general cannot be understood without considering digital religion. Religion encounters a particularly conducive environment for transformation processes on social media platforms such as the transformation process of polarization with the creation of progressive and conservative religious identities. The theoretical framework presented in this paper provides a foundation for future empirical research on polarization in religion, as its broader examination is necessary to develop a more comprehensive understanding of this phenomenon and thus of contemporary religion in general.